Explaining aid (in)effectiveness - Brett, Edwin A. (Department of International Development, London School of Economics and Political Science, 2016)
International aid plays an ambivalent and contested role in stabilising the global system. It creates asym-metrical relationships between donors and recipients that succeed when their interests can be can harmo-nised but not when they conflict. Donors use their support to persuade sovereign governments to adopt pol-icies they support but cannot always negotiate acceptable settlements with them, producing non-compliance and failed programmes. These relationships and strategies have changed radically since the war in response to changes in the global system, policy paradigms, and crises. We review these processes, treat-ing aid relationships as a structural component of the global system; review the different strategies adopted by donors since the war that culminated in the recent Paris Declaration and Sustainable Development Goals calling for poverty reduction and good governance. We identify the political challenges that donors con-front in addressing these issues, and examine the strengths and weaknesses of their attempts to use of Polit-ical Economy Analysis and New Public Management to address them.
10419/224802
Keywords: Graue Literatur; Entwicklungszusammenarbeit; Internationale Kooperation; Effektivität; Politische Ökonomie; Global; Development policy cooperation; Armutsbekämpfung; Poverty alleviation; Aid effectiveness; Aid Relationships; pro-poor policies; political economy analysis; Paris Declaration; fragile states; democratisation; Sustainable Development Goals; New Public Management